2016
DOI: 10.1371/journal.pone.0159113
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Public’s Reservations about Broad Consent and Study-By-Study Consent for Donations to a Biobank: Results of a National Survey

Abstract: Researchers and policymakers do not agree about the most appropriate way to get consent for the use of donations to a biobank. The most commonly used method is blanket—or broad—consent where donors allow their donation to be used for any future research approved by the biobank. This approach does not account for the fact that some donors may have moral concerns about the uses of their biospecimens. This problem can be avoided using “real-time”—or study-by-study—consent, but this policy places a significant bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…We also found that for >70% of respondents, willingness to give broad consent was adversely affected by at least one scenario and that lower levels of trust in biomedical research was a strong predictor of this effect [8]. Further, when our respondents were asked to evaluate alternative forms of consent, substantial minorities found both broad and 'real-time' specific consent (in which the biobank asks for donor consent for each specific project) to be 'unacceptable' policies (43.6% and 43%, respectively) or to be the 'worst' policies (37.8%, 45%) among five options [9].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…We also found that for >70% of respondents, willingness to give broad consent was adversely affected by at least one scenario and that lower levels of trust in biomedical research was a strong predictor of this effect [8]. Further, when our respondents were asked to evaluate alternative forms of consent, substantial minorities found both broad and 'real-time' specific consent (in which the biobank asks for donor consent for each specific project) to be 'unacceptable' policies (43.6% and 43%, respectively) or to be the 'worst' policies (37.8%, 45%) among five options [9].…”
Section: Introductionmentioning
confidence: 93%
“…The survey administered to participants was the same one used in our previous national study [9]. It starts with a brief description of a fictional biobank and an explanation of the process of donating to a biobank.…”
Section: Surveysmentioning
confidence: 99%
“…Questions around what constitutes an optimal model for the consent of health research participants, and the limits of that consent, have been closely and extensively scrutinised in the academic literature. There remains disagreement on terminology as between broad and blanket consents (De Vries et al 2016) and in particular as to whether broad consent can, or cannot, be sufficiently informed in ethically robust terms Kaye et al 2014). A comprehensive review of this ongoing debate falls outside of the scope of this chapter.…”
Section: Models Of Consentmentioning
confidence: 99%
“…The authors further suggest that this interactive aspect of broad consent may be improved though the use of some of the communication methods used in dynamic consent (see also Kaye et al 2014 for a description of this model). De Vries et al (2016) suggest that the challenge in broad consent is to combine 'transparency about sponsored research together with governance models that assure the donor community and the public that their interests and moral concerns are being respected'. In the case of live donors to biobanks, they note that this can be achieved through access to information -for example by providing up-to-date descriptions of projects.…”
Section: Models Of Consentmentioning
confidence: 99%
“…Questions around what constitutes an optimal model for the consent of health research participants, and the limits of that consent, have been closely and extensively scrutinised in the academic literature. There remains disagreement on terminology as between broad and blanket consents (De Vries et al 2016) and in particular as to whether broad consent can, or cannot, be sufficiently informed in ethically robust terms (Sheehan 2011;Kaye et al 2014). A comprehensive review of this ongoing debate falls outside of the scope of this chapter.…”
Section: Models Of Consentmentioning
confidence: 99%